Between skins : Animal skins in the Iron Age and historical burials in eastern Fennoscandia - Kirkinen, Tuija (Helsingin yliopisto, 2019)
This thesis investigates the skin and fur finds which have been excavated from Iron Age (500 BC – AD 1200/1300) and historical (1200/1300–1700) burials in eastern Fennoscandia during the past 130 years. The research material is unique in Europe, as fur remains usually decompose in archaeological contexts. For eastern Fennoscandian Iron Age research, this study brings new information on the roles that animal skins and wild animals held in societies, which produced furs both for domestic use and for the international fur trade. The main questions of this thesis are 1) How can archaeological fur remains be studied? What information do they provide? 2) What kinds of furs have been discovered in the graves? 3) Why were the furs placed in the graves? 4) What are the recommendations for future research? The research material consists of skin remains from 121 inhumation burials (animal skins and hairs) and 22 cremation burial sites (remains of claws). Animal hairs were found especially in contact with metals. Hairs were also found from the Late Neolithic soil samples in Perttulanmäki Corded Ware burial in Kauhava, which evidences the huge potential of microarchaeological analysis in fibre research. In cremation cemeteries, the predator 3rd phalanges provide evidence for the cremation of brown bear and lynx skins. Animal skins were identified by species by the morphology of the hairs. The method was applied to the identification of species, fur preparation traditions like pulling, and the qualities of origin animals, such as the colour of the coat. In this thesis, morphological identification of hairs proved its usefulness as a cost-effective method for identifying archaeological samples. First, it can be applied in cases that lie outside the scope of scientific methods. These constraints are met when the sample size is very small, when the material is mineralized or when DNA has degenerated in acidic soils. However, most archaeological samples had undergone several taphonomic processes, caused especially by bacterial ...